1999
DOI: 10.1116/1.581686
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Ga–CH3 bond at cryogenic temperatures using atomic hydrogen. Adsorbed trimethylgallium reactivity

Abstract: The chemical interaction of adsorbed trimethylgallium and atomic hydrogen was investigated on a powdered silicon dioxide substrate containing various coverages of hydroxyl groups. The adsorption of trimethylgallium occurs nondissociatively at 128 K. Desorption of trimethylgallium occurs near 160 K by a nondissociative route. Atomic hydrogen, produced on a hot tungsten filament, reacts with adsorbed trimethylgallium at 128 K. This reaction produces infrared absorbances characteristic of dimethylgalliumhydride d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The sharp peak at 999 cm À1 agrees well with the Zr-H stretch vibration observed following exposure of ZrB 2 (0001) to H 2 (g) 36,37. In an IR study of TMG on a silicon dioxide surface, Mawhinney et al reported a shift of $11 cm À1 toward higher frequency for d s (CH 3 ) and d as (CH 3 ), which they attributed to the loss of one CH 3 group as TMG was transformed to dimethylgallium (DMG) 44. Furthermore, the intensities of the IR peaks of the CH 3 groups of DMG were much weaker than those of TMG.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The sharp peak at 999 cm À1 agrees well with the Zr-H stretch vibration observed following exposure of ZrB 2 (0001) to H 2 (g) 36,37. In an IR study of TMG on a silicon dioxide surface, Mawhinney et al reported a shift of $11 cm À1 toward higher frequency for d s (CH 3 ) and d as (CH 3 ), which they attributed to the loss of one CH 3 group as TMG was transformed to dimethylgallium (DMG) 44. Furthermore, the intensities of the IR peaks of the CH 3 groups of DMG were much weaker than those of TMG.…”
supporting
confidence: 60%
“…36,37 In an IR study of TMG on a silicon dioxide surface, Mawhinney et al reported a shift of $11 cm À1 toward higher frequency for d s (CH 3 ) and d as (CH 3 ), which they attributed to the loss of one CH 3 group as TMG was transformed to dimethylgallium (DMG). 44 Furthermore, the intensities of the IR peaks of the CH 3 groups of DMG were much weaker than those of TMG. The broad feature at 1221 cm À1 is 25 cm À1 higher than the highest d s (CH 3 ) peak at 1196 cm À1 [Fig.…”
Section: Methodsmentioning
confidence: 99%
“…GaMe 3 adsorbs reversibly on silica at cryogenic temperatures . Above 273 K, it reacts with the surface hydroxyl groups, liberating methane. The proposed reaction is shown in eq 1, where ⋮SiOH denotes a sterically accessible Q 3 site on the silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…GaMe 3 adsorbs reversibly on silica at cryogenic temperatures . Above 273 K, it reacts with the surface hydroxyl groups, liberating methane. The proposed reaction is shown in eq 1, where ⋮SiOH denotes a sterically accessible Q 3 site on the silica surface. In previous studies, the gallium product was formulated as a three-coordinate dimethylgallium(III) fragment, with a trigonal coordination environment similar to that of GaMe 3 both in the gas phase and in solution .…”
Section: Introductionmentioning
confidence: 99%